Improving Students’ Public Speaking Skills Through Religious Literacy Classes at Darussa’adah 3 in Jepara - Aris Rohmatin; Ahmad Saefudin (Institut Muslim Cendekia, 2026)
This study is motivated by the limited number of studies that specifically examine the role of literacy classes in strengthening santri’s public speaking skills in Islamic boarding schools, despite the importance of this skills for santri as future preachers and agents of social change. This study aims to describe the implementation of religious literacy classes and analyze their role in enhancing santri’s public speaking skills at Pondok Pesantren Darussa’adah 3 Bugel, Jepara. The study employed a qualitative, field-based design. The participants included the pesantren leader, the literacy class teacher, and some students who also supervises khitobah activities, and santri involved in the literacy program, selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using thematic analysis. The results indicate that religious literacy classes play a strategic role in improving santri’s confidence, courage, and readiness for communication through the integration of literacy activities and khitobah practice. This study concludes that religious literacy classes can serve as an effective model for developing public speaking skills in an Islamic boarding school. The implications of this study suggest that literacy-based learning can be adopted as a practical strategy to enhance students’ communication competence in similar educational contexts.